Risk scoring models for predicting peri-operative morbidity and mortality in people with fragility hip fractures: qualitative systematic review - Marufu, Takawira C.; Mannings, Alexa; Moppett, Iain K. (Elsevier, 2015)
Rationale: Accurate peri-operative risk prediction is an essential element of clinical practice. Various risk stratification tools for assessing patients’ risk of mortality or morbidity have been developed and applied in clinical practice over the years. This review aims to outline essential characteristics (predictive accuracy, objectivity, clinical utility) of currently available risk scoring tools for hip fracture patients. Methods: We searched eight databases; AMED, CINHAL, Clinical Trials.gov, Cochrane, DARE, EMBASE, MEDLINE and Web of Science for all relevant studies published until April 2015. We included published English language observational studies that considered the predictive accuracy of risk stratification tools for patients with fragility hip fracture. Results: After removal of duplicates, 15,620 studies were screened. Twenty-nine papers met the inclusion criteria, evaluating 25 risk stratification tools. Risk stratification tools considered in more than two studies were; ASA, CCI, E-PASS, NHFS and O-POSSUM. All tools were moderately accurate and validated in multiple studies; however there are some limitations to consider. The E-PASS and O-POSSUM are comprehensive but complex, and require intraoperative data making them a challenge for use on patient bedside. The ASA, CCI and NHFS are simple, easy and inexpensive using routinely available preoperative data. Contrary to the ASA and CCI which has subjective variables in addition to other limitations, the NHFS variables are all objective. Conclusion: In the search for a simple and inexpensive, easy to calculate, objective and accurate tool, the NHFS may be the most appropriate of the currently available scores for hip fracture patients. However more studies need to be undertaken before it becomes a national hip fracture risk stratification or audit tool of choice.